+0  
 
0
82
4
avatar+203 

Let \(f(x) = x^3 + 3x ^2 + 4x - 7\) and \(g(x) = -7x^4 + 5x^3 +x^2 - 7\) . What is the coefficient of \(x^3\) in the sum f(x) + g(x)?

 Apr 30, 2021
 #1
avatar+2135 
+1

f(x) has x^3

g(x) has 5x^3

x^3 + 5x^3 = 8x^3

 

=^._.^=

 Apr 30, 2021
 #2
avatar+203 
+1

Thanks! :D

 Apr 30, 2021
 #3
avatar+2135 
0

You're welcome. :))

=^._.^=

catmg  Apr 30, 2021
 #4
avatar+2135 
0

I'm really sorry, but the answer is 6. 

x^3 + 5x^3 = 6x^3

I have no idea why I thought 1 + 5 = 8. 

 

=^._.^=

catmg  Apr 30, 2021

15 Online Users

avatar